Antimicrobial Activity of Silver Nanoparticles Synthesized From Waste Vegetable Fibers. (2015) - Jaybhaye, Sandesh V.
Abstract: The green synthesis and stability of silver nanoparticles (AgNPs) by the bio-reduction method was investigated. An aqueous extracts of the local waste vegetables fiber were used as reducing and stabilizing agents. The UV-Vis absorption spectroscopy was used to monitor the quantitative formation of AgNPs. The external morphology of AgNPs was studied using scanning electron microscopy (SEM). The AgNPs produced by bio-reduction method using waste vegetable fibers of Murraya koenigii, Moringa oleifera and Luffa acutangula extract showed more than four weeks stability at 10-15 o C. It was found. The AgNPs of uniform in size of 15-35 nm was used to study their antibacterial activity against S. aurous .